Tuning the luminescence color of Eu3+- and alkali-ion-codoped Sr2CaWO6 orange-red phosphors: Eu3+ site distribution and site-selective photoluminescence studies - Otsuka, Takahito; Oka, Ryohei; Cicconi, Maria Rita; de Ligny, Dominique; Hayakawa, Tomokatsu (APL Materials, 2024)
In this study, Eu3+- and alkali-ion (M+)-codoped Sr2CaWO6:x (Eu3+, M+) (x = 0.01–0.10) were synthesized via a solid-state reaction. The effects of different Sr/Ca ratios, types of monovalent metal ions (M+ = Na+, K+, and Li+), and doping concentrations were systematically investigated. The crystalline phase, photoluminescence (PL) properties, lattice site occupied by the Eu3+ ion, Eu3+ site distribution, and site-selective PL properties were evaluated by x-ray diffraction, PL/photoluminescence excitation (PLE) spectroscopy with a monochromatic light source, PL quantum efficiency (QE) measurements, and high-resolution PL/PLE spectroscopy with a wavelength-tunable laser. A dependence of the PL asymmetry ratio for the 5D0–7F1,2 transitions on the Sr/Ca ratio was identified and quantified for the first time. Based on the site-selective PL measurements, this behavior was ascribed to the enhancement of Eu3+ local distortion by Sr2+ substitution at the A site at lower Sr/Ca ratios (<2) and to the high symmetry of the ligand structure of EuO6 octahedra owing to Ca2+ substitution at the B site at higher Sr/Ca ratios (>2). The PLE results provided insight into the Eu3+ site distribution, which explained the orange-red PL and PL QEs of the synthesized phosphors.<br
Keywords: Doping; Photoluminescence excitation spectroscopy; Crystalline solids; Optical materials; Perovskites; Photoluminescence spectroscopy; X-ray diffraction; Quantum efficiency; Lasers; Ions and properties